The Influence of Game Based Learning on Student Motivation in the Digital Era: Literature Review - Putri, Mahdatul Aini; Herpratiwi, Herpratiwi; Firdaus, Rangga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to analyze the impact of Game-Based Learning (GBL) on students’ learning motivation in the digital era. The research design applied is in the form of a literature review, which collects data from various relevant national and international journals. Game-Based Learning (GBL) is an innovative teaching method that integrates game elements to create interactive, enjoyable, and effective learning experiences. The results indicated that GBL enhances intrinsic motivation among students, promotes active engagement, and develops 21st-century skills such as critical thinking, collaboration, and problem-solving. Tools such as Kahoot, Educandy, and Minecraft: Education Edition have been found to create an interactive and fun learning environment. The implementation of GBL is still hampered by issues such as the lack of technological infrastructures in schools and the lack of teacher training to integrate technology and games into the learning process in Indonesia. This study argues that overcoming these challenges will, therefore, make GBL effective in enhancing the quality of Indonesian education and in preparing children to face challenges in this digital era.